Spatiotemporal variation in ecological security of cropped lands and its determinants in key crop production areas in Henan Province - WANG Yanjie; WEI Xinyu; WANG Jinhui; SUN Mengyuan; WANG Zhifang; ZHOU Kai (Guan'gai paishui xuebao)
【Objective】 Ensuring the ecological security of cropped lands is a prerequisite for developing sustainable agriculture and safeguarding food security, which is influenced by various factors. In this paper, we analyse the spatiotemporal variation in ecological security of cultivated lands and its determinants in key agricultural production regions in Henan Province. 【Method】 The analysis was based on the pressure-state-response (PSR) model, comprehensive index approach, and resistance diagnosis model. In the analysis, we considered fifteen indicators to assess the changes in ecological security from 2007 to 2022 across the province. 【Result】 ① From 2007 to 2022, the ecological security of cultivated lands in the province initially declined before recovering, with the composite index increasing from 0.342 in 2007 to 0.435 in 2022. ② The ecological security of cropped lands varied significantly across the province, with heightened sensitivity in the central areas, general and comparative security in the eastern regions, and high sensitivity in remote areas. ③ Key factors affecting the ecological security of cropped land in the province included fertilizer application per unit area (26.1%), cultivated land per capita (18.69%), and per capita water resources (18.45%). 【Conclusion】 From 2007 to 2022, the ecological security of the cultivated lands in Henan Province has substantially shifted. The overall ecological security of the cropped land in the province is at a moderate level, underscoring the need to improve agricultural resource use efficiency, reduce fertilizer and pesticide application, and foster sustainable interactions between terrestrial ecosystems and food security. Priorities in improving ecological security of the agroecosystems in the province include optimizing fertilizer application and preserving cultivated lands. These findings provide baseline for developing sustainable land management to safeguard food security in the major agricultural production regions in Henan Province.